HGF/Met Signaling in Cancer Invasion: The Impact on Cytoskeleton Remodeling - Chuan Xiang; Junxia Chen; Panfeng Fu (2017)
The invasion of cancer cells into surrounding tissue and the vasculature is essential for tumor metastasis. Increasing evidence indicates that hepatocyte growth factor (HGF) induces cancer cell migration and invasion. A broad spectrum of mechanisms underlies cancer cell migration and invasion. Cytoskeletal reorganization is of central importance in the development of the phenotype of cancer cells with invasive behavior. Through their roles in cell mechanics, intracellular trafficking, and signaling, cytoskeleton proteins participate in all essential events leading to cell migration. HGF has been involved in cytoskeleton assembly and reorganization, and its role in regulating cytoskeleton dynamics is still expanding. This review summarizes our current understanding of the role of HGF in regulating cytoskeleton remodeling, distribution, and interactions.